MOTIVATION, STRATEGY, DIGITAL MARKETING: MSME SUREFIRE MOVES TO SURVIVE IN THE MIDST OF THE COVID-19 PANDEMIC - Rizky Firmansyah; Mochammad Galih S Wicaksono; Dwi Narulia; Ridoni Fardeni Harahap; Annisa Puspita Amalia (Pasundan International of Community Services Journal (PICS-J), 2021)
This service activity aims to analyze the needs and build a digitalization mindset for MSMEs in Malang City in facing the challenges of the Covid-19 Pandemic. Digital marketing strategies can be a bridge for MSMEs to reach a wider target market, so an interpersonal approach is needed to encourage business people to renew targeted marketing strategies. The method of implementing this activity consists of three stages, namely pre-implementation, implementation and post-implementation. The findings on the activity contain interesting facts, including MSMEs in Malang City do not experience capital problems, cash flow uncertainty causes a reduction in production activities, features on online platforms have not been used optimally and difficulties in compiling interesting content that can create interaction with the target market. Significant results were shown by MSME actors after participating in counseling and training activities, namely MSME actors were able to determine an online platform that could support their marketing system and some MSME actors were able to create interactions with consumers through digital activation to the purchase process from consumers. Apart from that, there are still many things that must be improved by MSME actors, especially in improving the quality of human resources and the digital marketing system.